POTENTIAL IMPACT OF FEUERSTEIN INSTRUMENTAL ENRICHMENT ON SELF-CONCEPT OF LEARNERS WITH BEHAVIOURAL PROBLEMS - Jeřábková, Kateřina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article was prepared within preparatory phase of research on impact of Feuerstein Instrumental Enrichment (FIE) on self-concept of learners with behavioural problems. Its goal is to reveal the current state in research field concerning this topic in the Czech Republic. The programme FIE has been used in the Czech Republic since 1999, mostly for learners with special educational needs. The theoretical and research sources mostly describe the impact of FIE on the development and change of cognitive structures, the development of the art of learning and thinking (metacognition). Moreover, as one of the secondary objectives is also mentioned the restoration of a positive self-concept of the learners, precisely in compliance with the criteria of the mediated learning experience, e.g. by increasing the sense of competence of the learners and by learning to regulate their own behaviour. Thus, it influences the formation of healthy self-concept, self-confidence and self-acceptance of individuals participating in FIE. Generally stated, people who have a negative self-concept and/or low self-confidence are more likely to exhibit problem behaviour, whether in the family, school or wider social environment. In the Czech provenance, we found three studies that primarily address the impact of FIE on learners with behavioural problems - first on learners with serious behavioural problems living in residential educational institutions, second on learners with ADHD and third on children with problem behaviour. We managed to find four studies that partially aim to determine the level of self-concept/confidence/self-esteem/self-acceptance of FIE attendees. Five studies then report on the effect of FIO on self-concept/self-confidence/self-esteem/self-acceptance and six other studies present the impact of FIO on behaviour change of attendees (mentioned mostly as a side effect because the studies primarily did not address these aims).